Evaluation of stress intensity factor for arbitrary and low-quality meshes using virtual grid-based stress recovery (VGSR). (15th March 2022) - Choi, Habeun; Cui, Huiru; Park, Kyoungsoo
Highlights: The use of the virtual grid-based stress recovery (VGSR) is proposed to accurately compute the stress intensity factors (SIFs). VGSR can be utilized for arbitrary and low-quality meshes in 2D and 3D. VGSR reduces errors associated with the numerical differentiation and the integral domain of J -integral. VSGR reduces the stress oscillation caused by low-quality elements and provides more accurate evaluation of SIFs for arbitrary and low-quality meshes. Abstract: To accurately compute the stress intensity factors (SIFs) with arbitrary and low-quality meshes, the use of the virtual grid-based stress recovery (VGSR) technique is proposed for both 2D and 3D fracture problems. A virtual grid is generated along the crack front to reduce errors associated with the numerical differentiation and the integral domain for J -integral. Based on the displacement and stress fields in the virtual grid, SIFs are evaluated using the domain integral method. The accuracy and convergence of VGSR are demonstrated by solving mode-I and mixed-mode examples. Computational results demonstrate that VSGR reduces the stress oscillation caused by low-quality elements and provides more accurate evaluation of SIFs for arbitrary and low-quality meshes.